Discriminatory Precision of Neutrophil Gelatinase-Associated Lipocalin in Detection of Urinary Tract Infection in Children: a Systematic Review and Meta-Analysis - Abbasi, Arash; Nabizadeh, Fardin; Gardeh, Maryam; Ali, Kosar Mohamed; Yousefifard, Mahmoud; Hosseini, Mostafa (Archives of Academic Emergency Medicine, 2020)
Introduction: There is a significant discrepancy between studies on diagnostic precision of neutrophil gelatinase-associated lipocalin (NGAL) in diagnosis of urinary tract infection (UTI). Therefore, the present systematic review and meta-analysis was designed to assess the diagnostic value of NGAL in diagnosis of UTI in children and adolescents. Methods: An extensive search was performed on Medline, Embase, Scopus and Web of Science databases by the end of 2019. Two independent researchers screened and summarized the data. Discriminatory precision of urinary and serum NGAL was assessed by reporting area under the curve, sensitivity, specificity and diagnostic odds ratio with 95% confidence interval (95% CI). Results: Data from 12 studies were included. The area under the curve of urinary and serum NGAL for diagnosis of UTI in children and adolescents at the best cut-off point (between 30-39.9 ng/ml) was 0.95 (95% CI: 0.93 to 0.97) and 0.83 (95% CI: 0.80 to 0.86), respectively. Sensitivity, specificity and diagnostic odds ratio on urinary NGAL at these cut-off points were 0.89 (95% CI: 0.64 to 0.97), 0.89 (95% CI: 0.71 to 0.97) and 67 (95% CI: 5 to 891), respectively. Sensitivity, specificity and diagnostic odds ratio of serum NGAL in UTI detection were 0.85 (95% CI: 0.70 to 0.90), 0.81 (95% CI: 0.69 to 0.88) and 9.53 (95% CI: 1.52 to 59.65), respectively. Conclusion: The present meta-analysis showed that urinary NGAL had a high diagnostic value in detection of UTI in children and adolescents with an optimum cut-off point in the range of 30-39.9 ng/ml.